Multiple factors affect the regeneration of liver - Ouyang,Gaoxiong (2018)
SUMMARY OBJECTIVE To study factors affecting the liver regeneration after hepatectomy METHODS With 3D reconstitution technology, liver regeneration ability of 117 patients was analysed, and relative factors were studied. RESULTS There was no statistically difference between the volume of simulated liver resection and the actual liver resection. All livers had different degrees of regeneration after surgery. Age, gender and blood indicators had no impact on liver regeneration, while surgery time, intraoperative blood loss, blood flow blocking time and different ways of liver resection had a significant impact on liver regeneration; In addition, the patients’ own pathological status, including, hepatitis and liver fibrosis all had a significant impact on liver regeneration. CONCLUSION 3D reconstitution model is a good model to calculate liver volume. Age, gender, blood indicators and biochemistry indicators have no impact on liver regeneration, but surgery indicators and patients’ own pathological status have influence on liver regeneration.